Synthesis and electrochemical characterization of polyaniline doped cadmium oxide (PANI-CdO) nanocomposites for supercapacitor applications. (15th November 2022) - Anwar, Nadeem; Shakoor, Abdul; Ali, Ghulam; Ahmad, Haseeb; Niaz, Niaz Ahmad; Seerat-Ul-Arooj; Mahmood, Arshad
Abstract: High-performance nanoscale supercapacitor (SC) electrode materials of polyaniline (PANI) and polyaniline cadmium oxide (PANI-CdO) composites are fabricated using In-situ chemical polymerization route. The structural parameters, crystallite size, and lattice strain of the prepared samples are estimated by X-ray diffraction analysis. The CdO stretching peak in PANI-CdO nanocomposite's FTIR spectra confirms the interaction of CdO with PANI. SEM analysis exposing a random dispersion of CdO nanoparticles in PANI matrix and showing the cluster of indefinitely shaped fibrous flaky architectures. The cyclic voltammetry (CV) results show a higher specific capacitance of 866 F g −1 for PANI-5%CdO composite as compared to Pure PANI 222 F g −1 and Pristine CdO 35.2 F g −1 at 5 mV s −1 scan rate. Galvanostatic charge-discharge (GCD) results also show a higher specific capacitance value of 906.8 F g −1 for PANI-5%CdO composite at 9.26 A g −1 current density revealing a maximum energy density and power density of 9.04 Wh kg −1 and 1510 W kg −1 respectively. The frequency response behavior of PANI-CdO nanocomposites (EIS spectra) reveals (Warburg) diffusive resistance of the electrolyte into the interior of the electrode and ion diffusion into the electrode surface. The higher capacitance and lower ESR (equivalent series resistance) value of PANI-CdO nanocomposite refer to the formation of a more ordered structure and rapid ion diffusion that can develop enhanced surface-dependent electrochemical properties and recommend this material to be a promising potential candidate for practical supercapacitor electrode preparation. Highlights: The large surface-to-volume ratio and conductive nature of CdO lead to cost-effective and high-performance supercapacitor electrode materials. The increasing concentration of CdO in PANI-CdO composite leads to better rectifying behavior and decreasing built-in potential. The enhanced specific capacitance of PANI–CdO composites compared to Pure PANI and CdO at various sweep rates and non-linear redox properties reveal their pseudo-capacitive behavior, whereas a symmetrical trend describes the reversible performance of redox reactions. Which has not been studied yet to the best of our knowledge.